Effect of New Thiophene Derivatives on Isolated Rat Heart - Murthy, N.B.S.; Inamdar, M.N.; Mohan, S.; Kale, R. (Asian Journal of Chemistry, 2010)
Newer chemical entities (NCE) of thiophene class were synthesized by Gewald reaction and tested for influence on myocardial function in albino rats. Two potent antioxidant possessing agents (NCE-I and NCE-II) were selected for the study using modified Langendorff's method. Different concentrations of NCEs were evaluated for their effect on ischemia/reperfusion injury in isolated rat heart preparation by measuring the developed tension and resting tension. The results indicated that NCE-I had improved the functioning of ischemic myocardium upon reperfusion while NCE-II did not exhibit any beneficial effect on the functioning of cardiac muscle subjected to ischemia/reperfusion injury.